Cranial nerve involvement: its role in intracranial tuberculosis - Synmon, Baiakmenlang; Kayal, Ashok (International Journal of Research in Medical Sciences, 2020)
Background: Tubercular meningitis is the most severe form of extra pulmonary involvement. Lack of specific and sensitive test calls for a multi-displinary and combined approach to make the diagnosis at the earliest. Various factors guide us to the etiology of meningoencephalitis but cranial nerve involvement has the highest predictive value. Methods: A prospective study from August 2013 to September 2015 carried in GMCH, Guwahati where 93 patients of intracranial tuberculosis was included. Results: This present study comprised of 36 females (38.7%) and 57 males (61.3%) with a mean age of 32.3±17.05 and a range of 2-72 years. The typical clinicalfeatures of meningitis was found in 78.6%. Focal neurological deficit and cranial nerve involvement was seen in 40 (43%) and 58 (62.4%) respectively. Among the cranial nerves (CN), the most commonly involved is the 2nd CN seen in 33 (35.5%), followed by 6th (16.1%), 7th (11.8%), 3rd (7.5%), 8th (3.2%), 9th and 10th, (2.2%) 4th (1.1%) and 5th (1.1%). Six patients developed visual loss and two patients hearing loss as sequelae. The presence of cranial nerve involvement and focal neurological deficit was shown to be associated with a poor prognosis (p value=0.04**, significant; Fisher’s exact test). Conclusions: Bedside clinical examination of patients of meningoencephalitis to detect cranial nerve involvement will definitely help us with the diagnosis and prognosis of tubercular meningitis.